Physical, chemical and sensory evaluation of meat from cobia (rachycentron canadum), desensitized with different voltages of electric shock, stored under refrigeration - Melo,Fúlvio Viegas Santos Teixeira de (2019)
ABSTRACT: Fish quality is conditioned by several factors, among them desensitization methods applied for fish managing and slaughtering. This research used electric shock at different intensities as a desensitization method for cobia (Rachycentron canadum) slaughtering and evaluated its effects over fish quality during refrigerated storage. The experiment was carried out by numbing the fish with electroshock at the intensities of 100, 150 and 200 Volts, and keeping them in refrigerated storage for 21 days. On the cobia, obtained from a commercial fish farm the following physical, chemical and sensorial characteristics as quality variables were evaluated: dielectric properties, rigor index, pH, texture, color, sensorial evaluation of freshness, ATP and degradation catabolites. The experimental design was a 6×3 factorial (6 times of analysis and 3 electroshock intensities). Significant differences (P<0.05) were observed for the analyzed variables, as a consequence of desensitization treatments and of storage time within each treatment. However, the number of variables affected by the treatment was smaller than the number of variables significantly affected by the storage time, and the interaction time×treatment was highly significant within the results reported. The best results for the parameters tested were obtained when the treatment at 150 volts intensity with the majority of analyzed variables held significant differences (P<0.05) among treatments. It was also concluded that cobia can be conserved in refrigerated storage within seven days after slaughtering using electro-narcosis as a method of desensitization.